Association Between Urinary Tract Infection in the First Trimester and Risk of Preeclampsia in Pregnant Women - Khan, Sarah Hameed; Nousheena, Syeda; Tahir, Muhammad Masood; Begum, Tanveer Jehan (Biological and Clinical Sciences Research Journal, 2025)
Urinary tract infection during pregnancy is a common clinical problem and has been implicated in adverse maternal and fetal outcomes. Preeclampsia remains a leading cause of maternal and perinatal morbidity and mortality worldwide, particularly in low and middle-income countries. Evidence suggests that infections occurring early in pregnancy may contribute to the pathogenesis of preeclampsia through inflammatory and immunological mechanisms; however, data from Pakistani populations remain limited. Objective: To determine the association between urinary tract infection in the first trimester and the risk of developing preeclampsia among pregnant women. Methods: This case-control study was conducted at the Department of Obstetrics and Gynaecology, Ibn-e-Siena Hospital, Multan, over six months, from November 2023 to May 2024. A total of 176 pregnant women were enrolled using non-probability consecutive sampling, including 88 women with preeclampsia and 88 normotensive controls. A urinary tract infection during the first trimester was identified through medical record review, based on urine examination and culture results. Demographic and obstetric variables were recorded, and data were analyzed using SPSS version 23. The association between first-trimester UTI and preeclampsia was assessed using chi-square testing and odds Ratio estimation, with stratification performed for potential confounders. Results: The mean age of participants was 29.4 ± 5.8 years. First-trimester urinary tract infection was significantly more frequent among women with preeclampsia compared to controls (37.5% vs. 20.5%, p = 0.01). Women with documented UTI had more than twice the odds of developing preeclampsia (OR 2.33; 95% CI: 1.18–4.59; p = 0.01). Stratified analysis demonstrated a persistent significant association across age groups, higher body mass index categories, and urban residence. Conclusion: Urinary tract infection during the first trimester is significantly associated with an increased risk of preeclampsia. Early screening and prompt management of UTIs during pregnancy may reduce the burden of preeclampsia and improve maternal outcomes.